Vascular Sema3E-Plexin-D1 Signaling Reactivation Promotes Post-stroke Recovery through VEGF Downregulation in Mice - Ri Yu; Nam-Suk Kim; Yan Li; Jin-Young Jeong; Sang-Joon Park; Bin Zhou; Won-Jong Oh (Translational Stroke Research, 2022)
Post-stroke vascular remodeling, including angiogenesis, facilitates functional recovery. Proper vascular repair is important for efficient post-stroke recovery; however, the underlying mechanisms coordinating the diverse signaling pathways involved in vascular remodeling remain largely unknown. Recently, axon guidance molecules were revealed as key players in injured vessel remodeling. One such molecule, Semaphorin 3E (Sema3E), and its receptor, Plexin-D1, control vascular development by regulating vascular endothelial growth factor (VEGF) signaling. In this study, using a mouse model of transient brain infarction, we aimed to investigate whether Sema3E-Plexin-D1 signaling was involved in cerebrovascular remodeling after ischemic injury. We found that ischemic damage rapidly induced Sema3e expression in the neurons of peri-infarct regions, followed by Plexin-D1 upregulation in remodeling vessels. Interestingly, Plexin-D1 reemergence was concurrent with brain vessels entering an active angiogenic process. In line with this, Plxnd1 ablation worsened neurological deficits, infarct volume, neuronal survival rate, and blood flow recovery. Furthermore, reduced and abnormal vascular morphogenesis was caused by aberrantly increased VEGF signaling. In Plxnd1 knockout mice, we observed significant extravasation of intravenously administered tracers in the brain parenchyma, junctional protein downregulation, and mislocalization in regenerating vessels. This suggested that the absence of Sema3E-Plexin-D1 signaling is associated with blood–brain barrier (BBB) impairment. Finally, the abnormal behavioral performance, aberrant vascular phenotype, and BBB breakdown defects in Plxnd1 knockout mice were restored following the inhibition of VEGF signaling during vascular remodeling. These findings demonstrate that Sema3E-Plexin-D1 signaling can promote functional recovery by downregulating VEGF signaling in the injured adult brain.